2020
DOI: 10.3390/machines8040084
|View full text |Cite
|
Sign up to set email alerts
|

Possible Applications of Additive Manufacturing Technologies in Shipbuilding: A Review

Abstract: 3D printing conquers new branches of production due to becoming a more reliable and professional method of manufacturing. The benefits of additive manufacturing such as part optimization, weight reduction, and ease of prototyping were factors accelerating the popularity of 3D printing. Additive manufacturing has found its niches, inter alia, in automotive, aerospace and dentistry. Although further research in those branches is still required, in some specific applications, additive manufacturing (AM) can be be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…This is the case of polyethylene terephthalate glycol (PETG), a mainstream recycled material used in the packaging industry and also used in the AM industry due to its processability together with its good behavior against corrosion and chemical and physical resistance [4]. Other industries using PLA and PETG are as following: medical due to the biocompatible characteristics of these materials [25], packaging [26,27] and maritime fields [28,29]. This research can be applied to the maritime and packaging industries due to the characteristics of product types and part requirements in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of polyethylene terephthalate glycol (PETG), a mainstream recycled material used in the packaging industry and also used in the AM industry due to its processability together with its good behavior against corrosion and chemical and physical resistance [4]. Other industries using PLA and PETG are as following: medical due to the biocompatible characteristics of these materials [25], packaging [26,27] and maritime fields [28,29]. This research can be applied to the maritime and packaging industries due to the characteristics of product types and part requirements in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 18 shows the successful implemented WAAMpeller by RAMLAB. The WAAMpeller has a diameter of 1.3 m, weight of 180 kg and was manufactured to drive a Stan Tug 1606 (Ziółkowski and Dyl [2020]. The whole manufacturing process was supervised and certified by Bureau Veritas.…”
Section: Naval and Offshore Applicationsmentioning
confidence: 99%
“…Most AM techniques focus on small processing chambers to produce small parts. The naval industry is characterized by large-size components, but it has been working gradually to use parts made by AM (Ziółkowski and Dyl [2020]). The global market is increasing the use of additive manufacturing technology and the titanium demand.…”
Section: Introductionmentioning
confidence: 99%
“…After almost four decades of research and development, AM has proved to be a remarkable manufacturing technique, with an ongoing optimization of design methodology, material variety, and processing. Today, metal components fabricated with AM have obtained the mechanical properties and corrosion resistance required by aerospace, automotive, biomedical, energy, and marine applications [1,2]. Furthermore, researchers have demonstrated that the AM technology generates significant cost savings compared to conventional manufacturing due to the reduction of lead times and less waste of raw materials.…”
Section: Introductionmentioning
confidence: 99%